Increased pulsatility index of the basilar artery is a risk factor for neurological deterioration after stroke: a case control study - Il-Han Yoo; Jeong-Min Kim; Su-Hyun Han; Jaiyoung Ryu; Keun-Hwa Jung; Kwang-Yeol Park (BMC, 2022)
Abstract Background Higher pulsatility of the middle cerebral artery (MCA) is known to be associated with stroke progression. We investigated whether pulsatility index (PI) of the basilar artery (BA) can predict neurological deterioration (ND) after acute cerebral infarction. Methods A total of 708 consecutive patients with acute ischemic stroke who had undergone transcranial Doppler (TCD) ultrasonography were included. ND was defined as an increase in the National Institutes of Health Stroke Scale scores by two or more points after admission. The patients were categorized into quartiles according to BA PI. Multivariable logistic regression analysis was performed to examine whether BA PI is independently associated with ND. Results BA PI was well correlated with the right (n = 474, r2 = 0.573, P < 0.001) by Pearson correlation analysis although MCA PI could not be measured from right MCA (n = 234, 33.05%) and left MCA (n = 252, 35.59%) by TCD owing to insufficient temporal bone window. Multivariable logistic regression analysis including age, sex, cerebral atherosclerosis burden, National Institutes of Health Stroke Scale at admission, and the proportion of patients with current smoking status, hypertension, diabetes mellitus, atrial fibrillation revealed that the higher BA PI (odds ratio, 3.28; confidence interval, 1.07-10.17; P = 0.038) was independently associated with ND. Conclusions BA PI, which would be identified regardless of temporal window, could predict ND among acute stroke patients.